MIR204 n.37C>T variant as a cause of chorioretinal dystrophy variably associated with iris coloboma, early-onset cataracts and congenital glaucoma - Jedlickova, Jana; Vajter, Marie; Barta, Tomas; Black, Graeme C M; Perveen, Rahat; Mares, Jan; Fichtl, Marek; Kousal, Bohdan; Dudakova, Lubica; Liskova, Petra (Clinical genetics, 2023)
Four members of a three-generation Czech family with early-onset chorioretinal dystrophy were shown to be heterozygous carriers of the n.37C>T in MIR204. The identification of this previously reported pathogenic variant confirms the existence of a distinct clinical entity caused by a sequence change in MIR204. Chorioretinal dystrophy was variably associated with iris coloboma, congenital glaucoma, and premature cataracts extending the phenotypic range of the condition. In silico analysis of the n.37C>T variant revealed 713 novel targets. Additionally, four family members were shown to be affected by albinism resulting from biallelic pathogenic OCA2 variants. Haplotype analysis excluded relatedness with the original family reported to harbour the n.37C>T variant in MIR204. Identification of a second independent family confirms the existence of a distinct MIR204-associated clinical entity and suggests that the phenotype may also involve congenital glaucoma.
Keywords: rodokmen; Glaucoma; Coloboma; Mutation; lidé; mikro RNA; katarakta; MicroRNAs; glaukom; mutace; Cataract; iris; Iris; Pedigree; Humans; kolobom